Privilege in the Soviet Union (Routledge Revivals) : a Study of Elite Life-Styles under Communism. - Matthews, Mervyn (Routledge revivals., 2013)
First published in 1978, this unique work throws much-needed light upon the exact nature of privilege and elite life-styles in the contemporary Soviet Union, under the Communist regime. Dr Matthews' study places these life-styles in a historical perspective, and characterises, in sociological terms, the people who enjoyed them. This study is based on an extensive programme of personal interviews among emigré groups and a close analysis of original and little-known legal historical sources. There are special sections on the nature of change in the Soviet elite and on social mo.